Digitalization and SME competitiveness in Sabah: A PLS-SEM analysis of infrastructure, implementation, and human capital - Sabu, Zainuddin; Taasim, Shairil Izwan; Daud, Adrian (Asian Journal of Empirical Research, 2025)
This study investigates the factors influencing the competitiveness of small and medium-sized enterprises (SMEs) in Sabah, focusing on the roles of human resources, infrastructure, and implementation. Addressing these issues is crucial to facilitate digital transformation among SMEs in Sabah and promote more inclusive economic development. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from SMEs across various districts in Sabah. The findings reveal that both infrastructure and implementation have significant and positive effects on competitiveness, supporting established theories that emphasize the importance of tangible assets and strategic execution in enhancing firm performance. However, contrary to much of the existing literature, human resources demonstrated a significant but negative relationship with competitiveness. This suggests that within the Sabah context, challenges such as limited skills, insufficient training, or misaligned HR strategies may be hindering SMEs' ability to leverage human capital effectively. The study contributes to the literature by offering context-specific insights into SME development in a geographically and economically diverse region, and it highlights the need for more targeted policies to strengthen human resource capabilities to support sustainable competitiveness.